2018
DOI: 10.1186/s12891-018-2113-8
|View full text |Cite
|
Sign up to set email alerts
|

Weight bearing versus non-weight bearing ankle dorsiflexion measurement in people with diabetes: a cross sectional study

Abstract: BackgroundAccurate measurement of ankle dorsiflexion is important in both research and clinical practice as restricted motion has been associated with many foot pathologies and increased risk of ulcer in people with diabetes. This study aimed to determine the level of association between non-weight bearing versus weight bearing ankle dorsiflexion in adults with and without diabetes, and to evaluate the reliability of the measurement tools.MethodsOne hundred and thirty-six adults with diabetes and 30 adults wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The test was completed three times, with 10 s rest between tests, and the average score was documented as the test result. The authors have previously shown this method to have excellent intrarater (ICC = 0.83 to 0.89) and interrater reliability (ICC = 0.88 to 0.93), so a single assessor recorded all the measurements in this study [ 12 ]. In-shoe plantar pressures were measured with the Novel Pedar-X ® system (Novel GmbH, Munich, Germany) which utilises flexible insoles that contain 99 capacitive sensors sampling at a frequency of 100 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…The test was completed three times, with 10 s rest between tests, and the average score was documented as the test result. The authors have previously shown this method to have excellent intrarater (ICC = 0.83 to 0.89) and interrater reliability (ICC = 0.88 to 0.93), so a single assessor recorded all the measurements in this study [ 12 ]. In-shoe plantar pressures were measured with the Novel Pedar-X ® system (Novel GmbH, Munich, Germany) which utilises flexible insoles that contain 99 capacitive sensors sampling at a frequency of 100 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…The average of the 3 trials scores was documented as the test result. Both feet were measured (Hall & Docherty, 2017;Langarika-Rocafort et al, 2017;Powden et al, 2015;Searle et al, 2018).…”
Section: Testing Sessionsmentioning
confidence: 99%
“…This condition has been demonstrated to compromise skeletal muscle function, even beginning early in life in many cases, what would indicate that muscle dysfunction is a primary diabetic complication (being more accelerated with the development of neuropathy) (Krause et al, 2011;Monaco et al, 2019). Hyperglycemia also promotes the increase in ankle stiffness even without the presence of neuropathy (Francia et al, 2018;Searle et al, 2017Searle et al, , 2018 and compromises dynamic balance, also in young patients with no complications diagnosed (Katsarou et al, 2017;Kukidome et al, 2017;Turcot et al, 2009), among other physiological complications. Because of that, T1DM causes the premature loss of lower limb strength (Celes et al, 2017;Monaco et al, 2019), PeerJ reviewing PDF | (2020:05:48640:2:1:NEW 6 Nov 2020)…”
Section: Introductionmentioning
confidence: 99%